Need Analysis of Story Book based on Ecopedagogy in Supporting Environmental Literacy in Elementary School - Hasanah, Uswatun; Edwita, Edwita; Adnan, Evita; Imaningtyas, Imaningtyas; Januar, Ahmad (Universitas Alma Ata, 2025)
Environmental literacy needs to be developed from an early age because early it can foster awareness and responsible behavior towards nature. Based on observation, public concern for the environment is currently a concern for many parties. This is evidenced by the large amount of garbage scattered in the surrounding environment, one of which is in the school environment. This causes learning to become uncomfortable because of polluted air and dirty environmental conditions. This study aims to analyze students' needs for the development of ecopedagogy-based storybook media. The study used a survey with a phenomenological approach to find out the reality in the field related to the condition of the elementary school environment. The respondents of this study were 20 elementary school teachers from three different schools in Setiabudi District, South Jakarta to provide information about the potential for student environmental literacy issues and the use and acceptance of current media in supporting students' environmental concerns. In addition, 100 students were also involved to measure their environmental literacy. Each school has different characteristics according to the facilities and conditions of the school. The findings show that environmental literacy possessed by students tends to be only cognitive in nature where the knowledge score is 75.5, the cognitive skills score is 63.78, the attitude score towards the environment is 60.08, while the behavior score towards the environment is only 54.76. The results prove that the students' knowledge score is higher than the students' attitudes and behavior towards the environment. On the other hand, based on observations and interviews, 80% of students and teachers strongly agree with the development of ecopedagogy-based story books. This media is a solution to stimulate students' environmental literacy. Therefore, ecopedagogy-based story book products need to be developed to improve students' environmental literacy.Keywords: environmental literacy; story books; ecopedagogy; elementary school